Online Gaming, Digital Entertainment, and Academic Performance among Students: A Review - Teuku Rizky Noviandy; Rinaldi Idroes (Heca Sentra Analitika, 2026)
Online gaming and digital entertainment have become increasingly integrated into students’ daily lives through smartphones, computers, gaming platforms, video streaming, and social media. This review paper examines the relationship between online gaming, digital entertainment, and academic performance among students. The discussion highlights that digital entertainment can produce both positive and negative effects depending on duration, timing, content type, self-regulation, and learning context. Moderate and purposeful use may support cognitive skills, social interaction, motivation, and digital literacy. In contrast, excessive or problematic use may contribute to distraction, reduced study time, poor sleep quality, lower learning engagement, and weaker academic outcomes. Quantitative findings from previous studies show that many students engage frequently in online gaming and digital entertainment, including long weekly gaming time, mobile gaming as a major source of entertainment, and frequent social media checking. Overall, the reviewed literature suggests that the relationship between digital entertainment and academic performance is conditional rather than absolute. Healthy digital habits, effective time management, and guidance from parents, teachers, and educational institutions are important to help students balance entertainment and academic responsibilities.